PLAYING METHODS TO INCREASE EARLY CHILDHOOD HAPPINESS - Epifania M. Ladapase (Sean Institute, 2023)
Children who are separated from their parents or from the nuclear family will affect the psychological condition of the child which is marked by a decrease in the child's happiness. Handling carried out on children is to provide treatment with the method of play. The purpose of this research is to find out the effectiveness of the play method in increasing early childhood happiness. This research is an experiment in the form of non randomized pre test-post test one group design , with one treatment. The instrument in this research is the happiness scale. Methods of data analysis using non-parametric (Wilcoxon). The results of the study prove that playing methods are effective in increasing early childhood happiness.